RETRACTED: The spirituality of the art of creating landscape-architectural biotechnological environment of cultural objects in the formation of the personality of the younger generation - Goryacheva Elena; Vlasova Irina; Semergei Margarita (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001